Warfare in Bronze Age society - Horn, Christian; Kristiansen, Kristian (Cambridge University Press, 2018)
"In this book, it is argued that the Bronze Age represents the global emergence of a militarized society with a martial culture, materialized in a package of new efficient weapons that remained in use for millennia to come. It is evidenced in the ostentatious display of weapons in burials and hoards, as well as in iconography, from rock art to palace frescoes (Osgood, Monks and Toms 2000). This development has been described in a variety of ways: as the emergence of warrior aristocracies (Kristiansen 1999; Treherne 1995; Vandkilde chapter this book), linked to the emergence of the 'Hero' and his retinue (Hansen 2014; Vandkilde postscript), or simply through a study of weapons and their indications of use (Harding 2007; Horn 2013; Kristiansen 1984 and 2002; Molloy 2007; Quillec 2007; Randsborg 1995). It all comes down to the historical fact that warfare becomes institutionalized and professionalized during the Bronze Age, a new class of warriors make their appearance, even if there were differences between Eurasia, the Mediterranean and Europe, rooted in their different social and political complexity. However, they were not bigger than warriors employed similar types of swords and warrior gear. The causes behind this development can be traced back to a combination of factors"--Provided by publisher.